Apolipoprotein E and plasminogen activator inhibitor 1 gene polymorphism in children with chronic renal insufficiency associated with cardiovascular disease - Bahia Hassan Moustafa; Ahmed Badr; Abeer Selim; Rania Samy; Nasser Gamal (SpringerOpen, 2019)
Abstract Background Cardiovascular disease (CVD) is considered a major cause of death in renal insufficiency (RI). Contributing genetic factors is a recent focus of research. This study aims to elucidate apolipoprotein E (APO-E) and plasminogen activator inhibitor 1 (PAI-1) gene polymorphisms in RI children associated with CVD. Methods We studied 50 cases with chronic kidney disease (CKD) associated with CVD, and 30 healthy controls. Study sample was grouped as one on conservative treatment, the second on hemodialysis and the third was posttransplant. PAI-1 and APO-E gene polymorphisms were investigated using allele-specific polymerase chain reaction (AS-PCR) and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) respectively. Results 4G4G and 4G5G were the most common PAI-1 polymorphism denoting high association of 4 G allele in renal insufficiency associated with CVD with absent link to dyslipidemia, echocardiography changes or thrombosis. E3E3 was the most common among APO-E polymorphism without relation to dyslipidemia or thrombosis. Dyslipidemia was significantly linked to thrombosis. The study confirmed the role of dyslipidemia and hemodialysis in promoting thrombosis. Conclusion Although PAI 4G Genotyping did not show significant association with echocardiography severity or thrombotic severity, yet genetic expression for high levels of PAI in plasma is expected in response to CRI factors known to trigger its release, in addition to those related to dialysis. APO-E3E3 genotyping showed a significant association with echocardiography severity as it enhances APO-A which contributes to CVD. The current study confirmed a significant association between dyslipidemia and CVD; however, the prevalent patterns 4G and E3E3 did not show a significant association with dyslipidemia. The genetic role for APO-A, B, O, or even other isomers for APO-E should be further studied as well.